Principal's instructional leadership skills and teachers' motivation level - Chua, Y.P.; Ab. Razak, N. (Leadership, 2010)
This study was carried out to identify relationship between a principal's instructional leadership skills and teachers' level of work motivation in school. Focus was given to four identified principal's instructional leadership skills, namely education leadership skills, complex problem, solving skills, communication skills and developing skills. A group of randomly selected secondary school teacher answered two questionnaires named 'The School Management Skills of the 21st Century and the 'Measures of Individual Differences in Achieving Tendency'. Results indicate that teachers' motivation was significantly and strongly correlated with the principal's instructional leadership skills. The funding imples that principal's instructional leadership skill is a factor of teachers' work motivation.